Evaluation of Manganese Cubanoid Clusters for Water Oxidation Catalysis: From Well-Defined Molecular Coordination Complexes to Catalytically Active Amorphous Films - Hosseinmardi, Soosan; Scheurer, Andreas; Heinemann, Frank Wilhelm; Kuepper, Karsten; Senft, Laura; Waldschmidt, Pablo; Ivanovic-Burmazovic, Ivana; Meyer, Karsten (Chemsuschem, 2021)
With a view to developing multimetallic molecular catalysts that mimic the oxygen-evolving catalyst (OEC) in Nature's photosystem II, the synthesis of various dicubanoid manganese clusters is described and their catalytic activity investigated for water oxidation in basic, aqueous solution. Pyridinemethanol-based ligands are known to support polynuclear and cubanoid structures in manganese coordination chemistry. The chelators 2,6-pyridinedimethanol (H2L1) and 6-methyl-2-pyridinemethanol (HL2) were chosen to yield polynuclear manganese complexes; namely, the tetranuclear defective dicubanes [MnII2MnIII2(HL1)4(OAc)4(OMe)2] and [MnII2MnIII2(HL1)6(OAc)2] (OAc)2⋅2 H2O, as well as the octanuclear-dicubanoid [MnII6MnIII2(L2)4(O)2(OAc)10(HOMe/OH2)2]⋅3MeOH⋅MeCN. In freshly prepared solutions, polynuclear species were detected by electrospray ionization mass spectrometry, whereas X-band electron paramagnetic resonance studies in dilute, liquid solution suggested the presence of divalent mononuclear Mn species with g values of 2. However, the magnetochemical investigation of the complexes’ solutions by the Evans technique confirmed a haphazard combination of manganese coordination complexes, from mononuclear to polynuclear species. Subsequently, the newly synthesized and characterized manganese molecular complexes were employed as precursors to prepare electrode-deposited films in a buffer-free solution to evaluate and compare their stability and catalytic activity for water oxidation electrocatalysis.
CRIS-Team Scopus Importer:2021-10-08
Keywords: cubanes; electrocatalysis; electrodeposition; manganese; water splitting